2003
DOI: 10.1073/pnas.1633392100
|View full text |Cite
|
Sign up to set email alerts
|

Polyserase-I, a human polyprotease with the ability to generate independent serine protease domains from a single translation product

Abstract: We have identified and cloned a human liver cDNA encoding an unusual mosaic polyprotein, called polyserase-I (polyserine protease-I). This protein exhibits a complex domain organization including a type II transmembrane motif, a low-density lipoprotein receptor A module, and three tandem serine protease domains. This unusual modular architecture is also present in the sequences predicted for mouse and rat polyserase-I. Human polyserase-I gene maps to 19p13, and its last exon overlaps with that corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 46 publications
6
67
1
Order By: Relevance
“…It is remarkable that the fluorescent signal can be detected only if the polyserase-2 transfected cells have been previously permeabilized but is absent if samples were not treated with Triton X-100 (data not shown). This situation clearly differs from that observed in polyserase-1, in which the corresponding fluorescent signal can be detected without permeabilization of the cells, as a consequence of its membrane localization (10). According to this finding, we conclude that polyserase-2 is not a membrane-anchored protein and that it is likely secreted to the extracellular medium.…”
Section: Production Of Recombinant Polyserase-2 In Transfected Human contrasting
confidence: 88%
See 4 more Smart Citations
“…It is remarkable that the fluorescent signal can be detected only if the polyserase-2 transfected cells have been previously permeabilized but is absent if samples were not treated with Triton X-100 (data not shown). This situation clearly differs from that observed in polyserase-1, in which the corresponding fluorescent signal can be detected without permeabilization of the cells, as a consequence of its membrane localization (10). According to this finding, we conclude that polyserase-2 is not a membrane-anchored protein and that it is likely secreted to the extracellular medium.…”
Section: Production Of Recombinant Polyserase-2 In Transfected Human contrasting
confidence: 88%
“…Thus, both proteases contain three tandem serine protease domains in their respective amino acid sequences. However, the polyserase-2 architecture is less complex because of the lack of additional domains such as a type II transmembrane sequence and a low-density lipoprotein receptor A module present in polyserase-1 (10). Consistent with these structural differences, experimental analysis demonstrated that polyserase-2 is detected as a soluble protease, whereas polyserase-1 is associated with the plasma membrane through its type II transmembrane sequence.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations